Some Adventures of the Boys: Enniskillen Township's "Foreign Drillers," Imperialism, and Colonial Discourse, 1873-1923 - Burr, Christina (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract This paper analyses the travel writings composed by the oil drillers from Enniskillen township, in southwestern Ontario, to explain how they went about reinforcing the project of European capitalist imperialism while simultaneously disavowing the agency of native "Others." As British subjects and Anglo-Canadians, travel and travel writing helped to define Enniskillen's "foreign drillers" as both colonizers and colonized. As agents of imperialism Enniskillen drillers became part of an imperial overclass by virtue of their "whiteness," "Britishness," and technical expertise in the mining and refining of petroleum. The colonial oil fields also became a space for the re-invention of Victorian ideals of domesticity. The wives and children of foreign drillers also travelled abroad with their husbands. In their role as homemakers, women also reinforced imperialism and its hierarchies of race and class.